VIOLENCE IN RECREATIONAL NIGHTLIFE. THE RELATION BETWEEN ALCOHOL AND DRUG CONSUMPTION AND THE RECREATIONAL HABITS OF PORTUGUESE YOUTH" - Lomba, Maria de Lurdes Lopes de Freitas (2011)
Recreational nightlife is becoming increasingly important in the life of young people today: it determines lifestyles, and normalizes recreational alcohol and drug consumption and the adoption of other risky behaviors, among which this study highlights violent behavior. The objective of this study is to identify the profile of the Portuguese youth who attend entertainment venues and determine the prevalence of violent behavior associated with sociodemographic variables, alcohol and drug consumption, and participation in recreational nightlife activities. Respondent-driven sampling was used to survey 1346 young people of both sexes with a mean age of 22.49 years in 10 Portuguese cities. Results show that they have regular habits of going out at night, especially on weekends. The most used substances are alcohol, cannabis, cocaine and ecstasy. In the last 12 months, in recreational nightlife venues, 2.76% carried weapons, 8.55% were threatened/injured with a weapon and 8.17% were involved in physical fights. There was a positive correlation between how often young people were in fights or were threatened/injured and the consumption of alcohol and drugs, and with their engagement in recreational activities. Regarding the carrying of weapons, this connection was noted in relation to the consumption of cannabis, alcohol abuse and the number of nights young people went out per month. Young males and young people with lower education most often adopt the violent behaviors under analysis. Young people of a lower socioeconomic status carry weapons more often than young people of an upper or upper-middle status, but these latter get involved in fights more often or are threatened/injured more often. Younger people are the ones who fight most often. It is suggested that preventive measures should be implemented in recreational contexts, bearing in mind the characteristics of young people which are identified in this study as predictors of violent behaviors.